Peculiarities of bitumen testing methods - Tulebekova, A.; Kusbergenova, Zh.; Aldungarova, A.; Bakirbayeva, A. (Eurasian Journal of Applied Engineering and Technology (EJAET), 2022)
Bitumen as a construction material is extremely widespread in hydraulic engineering and road construction. Bitumen has a wide variety of features and useful properties, which allowed it to reach a leading level among other binder building materials. The article presents the peculiarities of laboratory testing of bitumen. Step by step the technique of bitumen testing on the ring-ball device and on the ductilometer is disclosed. The importance of testing quality control is justified. The results obtained showed the absence of deviations from the normative values. And reliability and accuracy of the obtained results are reached due to the use of an analytical approach and taking into account the risks arising during the tests. The account of which is presented by means of the "bow-tie" methodology, the main advantages of the use of which are the analysis of the reasons for risk occurrence, and the determination of decisions on their elimination.